Macroeconomic Policy in a Heterogeneous Monetary Union - Oliver Grimm; Stefan Ried (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
We use a two-country model with a central bank maximizing union-wide welfare and two fiscal authorities minimizing comparable, but slightly different country-wide losses. We analyze the rivalry between the three authorities in seven static games. Comparing a homogeneous with a heterogeneous monetary union, we find welfare losses to be significantly larger in the heterogeneous union. The best-performing scenarios are cooperation between all authorities and monetary leadership. Cooperation between the fiscal authorities is harmful to both the whole union's and the country-specific welfare.
Keywords: E52; E61; F42; 330; monetary union; heterogeneities; policy game; simultaneous policy; sequential policy; coordination; discretionary policies; Währungsunion; Finanzpolitik; Geldpolitik; Wohlfahrtsanalyse; Spieltheorie